Pelvic floor muscle evaluation in incontinent patients - Amaro, João Luiz [UNESP]; Moreira, ECH; Gameiro, MDO; Padovani, Carlos Roberto [UNESP] (Springer, 2005)
The aim of this study was to assess pelvic floor muscle (PFM) strength and perception and its correlation with stress urinary incontinence (SUI). One hundred and one women were divided into two groups according to the presence (G1=51 patients) or absence (G2=50 patients) of SUI. Subjective [urine stream interruption test (UST), visual survey of perineal contraction and transvaginal digital palpation to assess pelvic muscle contraction] and objective evaluations of pelvic floor muscles in all patients were performed (vaginal manometry). During the UST, 25.5% of G1 patients and 80% of G2 patients were able to interrupt the urine stream (p<0.05). Digital evaluation of pelvic muscular contraction showed higher strength in G2 than in G1 patients (p<0.0001). Perineometer evaluation of PFM strength was significantly higher in the continent group (p<0.001). Pelvic floor muscle weakness in incontinent patients demonstrates the importance of functional and objective evaluation of this group of muscles.
Keywords: pelvic floor muscle strength; urinary incontinence